1999
DOI: 10.1073/pnas.96.5.2532
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of regional cerebral blood flow and change of plasma sodium concentration during genesis and satiation of thirst

Abstract: Positron emission tomography studies were conducted during genesis of moderate thirst by rapid i.v. infusion of hypertonic saline (0.51 M) and after satiation of thirst by drinking water. The correlation of regional cerebral blood f low with the change in the plasma Na concentration showed a significant group of cerebral activations in the anterior cingulate region and also a site in the middle temporal gyrus and in the periaqueductal gray. Strongest deactivations occurred in the parahippocampal and frontal gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 31 publications
(26 reference statements)
8
68
0
4
Order By: Relevance
“…Previous reports from this group have identified activations associated with thirst (13,14,26) and plasma Na (27) in two regions of the cingulate cortex: the pACC and the aMCC (summarized graphically in ref. 28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from this group have identified activations associated with thirst (13,14,26) and plasma Na (27) in two regions of the cingulate cortex: the pACC and the aMCC (summarized graphically in ref. 28).…”
Section: Discussionmentioning
confidence: 99%
“…24 We ,5,6 and others 25,26 have observed activation of the insula in response to hunger and the sight of food in hungry people. Thus, analogous to the activation of this region in response to a variety of other cravings, [27][28][29] the increase in neural activity in the middle The change in regional cerebral blood flow (rCBF) is expressed in counts per voxel per minute (mean7s.e.m. and [range]).…”
Section: Discussionmentioning
confidence: 99%
“…A statistical parametric map of the pain response was generated by contrasting noxious pressure (scans 2, 4, 9, and 10) with no pressure (scans 1, 3, 8, and 11). A maximum thirst statistical parametric map was generated by contrasting the baseline (scans 1-4) with maximum thirst (scans [8][9][10][11]. Interactions between pain and maximum thirst were tested by contrasting concurrent pain and thirst (scans 9 and 10) with maximum thirst (scans 8 and 11) and pain (scans 2 and 4) in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of thirst-related brain activity have identified a network including the hypothalamus, thalamus, insula, parahippocampus, somatosensory cortex, anterior cingulate, posterior cingulate, and cerebellum (1,(10)(11)(12). A metaanalysis of pain imaging studies revealed a consistent network incorporating activity in the diencephalon and posterior parietal, insula, and limbic cortices and cerebellum (13).…”
mentioning
confidence: 99%